2013
DOI: 10.1002/chem.201300546
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Ring through a Room Temperature Catalytic Wittig Reaction

Abstract: One ring no longer rules them all: Employment of 2.5-10 mol % of 4-nitrobenzoic acid with phenylsilane led to the development of a room temperature catalytic Wittig reaction (see scheme). Moreover, these enhanced reduction conditions also facilitated the use of acyclic phosphine oxides as catalysts for the first time. A series of alkenes were produced in moderate to high yield and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 35 publications
2
72
0
Order By: Relevance
“…These reactions are similar to those mentioned previously by O’Brien’s group [20] that involve the cycling between 1 and 2 using a silane reducing reagent.…”
Section: Reviewsupporting
confidence: 81%
See 1 more Smart Citation
“…These reactions are similar to those mentioned previously by O’Brien’s group [20] that involve the cycling between 1 and 2 using a silane reducing reagent.…”
Section: Reviewsupporting
confidence: 81%
“…Subsequently they reported that the soluble organic base N , N -diisopropylethylamine was a good replacement for sodium carbonate in such reactions [19], and that the addition of 4-nitrobenzoic acid facilitated the phosphine oxide reduction step using phenylsilane (PhSiH 3 ) instead of diphenylsilane [20]. Using this combination of 4-nitrobenzoic acid and phenylsilane for phosphine oxide reduction allowed reactions starting with phosphine oxide 24 (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…An extension of the reaction time was not attempted in these cases, since the mass balance indicated significant decomposition of the starting materials. First, a set of four bases (NEt 3 , NaHCO 3 , K 2 CO 3 and NaOAc) and four solvents (MeCN, toluene, THF and DMF) were evaluated (entries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. While toluene and THF did not facilitate coupling in combination with most bases, the best results were obtained with DMF as the solvent (entries 15-18).…”
Section: Resultsmentioning
confidence: 99%
“…The esterification of cyclic phosphinic acids such as 1-hydroxy-3-phospholene oxides (7 and 8), 1-hydroxyphospholane oxides (11 and 13), and 1-hydroxy-1,2,3,4,5,6-hexahydrophosphinine oxide (15) was carried out in the presence of c. 15-fold excess of the alcohols in a closed vessel to afford the phosphinates (9, 10, 12, 14, and 16) in acceptable to excellent (44-95%) yields [33][34][35][36][37]. The method elaborated seems to be of general value.…”
Section: Direct Esterification and Amidation Of Cyclic Phosphinic Acidsmentioning
confidence: 99%